2020
DOI: 10.2147/opth.s231402
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of the Intraocular Pressure-Lowering Efficacy and Safety of the Brinzolamide/Brimonidine Fixed-Dose Combination versus Concomitant Use of Brinzolamide and Brimonidine for Management of Open-Angle Glaucoma or Ocular Hypertension</p>

Abstract: Objective: To demonstrate that the intraocular pressure (IOP)-lowering efficacy of a twice-daily brinzolamide 10 mg/mL (BRINZ)/brimonidine 2 mg/mL (BRIM) fixed-dose combination (BBFC) was non-inferior to its individual components (BRINZ+BRIM) dosed concomitantly in patients with open-angle glaucoma (OAG) or ocular hypertension (OHT). Safety was also evaluated. Methods and Analysis: This was a Phase III, multicenter, observer-masked study in patients from China, Russia and Taiwan. Patients aged ≥18 years with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Previous studies in the literature reported adverse drug reactions similar to those in our study after BBFC. 7 , 15 , 16 , 17 , 18 , 19 , 20 Similar to our study, Lerner et al 7 , reported that the rate of ocular adverse effects was 11.9% in patients who received maximum medical therapy in the form of BBFC and a beta-blocker/PG analog. In the same study, ocular adverse effects were observed in 7.5% of the control group given the beta-blocker/PG analog combination alone.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous studies in the literature reported adverse drug reactions similar to those in our study after BBFC. 7 , 15 , 16 , 17 , 18 , 19 , 20 Similar to our study, Lerner et al 7 , reported that the rate of ocular adverse effects was 11.9% in patients who received maximum medical therapy in the form of BBFC and a beta-blocker/PG analog. In the same study, ocular adverse effects were observed in 7.5% of the control group given the beta-blocker/PG analog combination alone.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the results of their study, the authors suggested that BBFC is an effective alternative for patients in whom IOP is not adequately controlled with brinzolamide or brimonidine alone, or in patients with contraindications to PG analog and beta-blockers. Similarly, Wang et al 16 compared treatment regimens including BBFC and separate brinzolamide and brimonidine drops together in patients with POAG and OHT and found both treatment regimens to have similar efficacy and safety. Kozobolis et al 17 compared the efficacy of BBFC and a dorzolamide/timolol fixed combination in 44 patients and reported a comparable IOP-lowering effect and safety profile.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the present study, mean reduction in IOP after 6 weeks of [17]. In the present study, mean IOP reduction at the end of 6 weeks was statistically similar between the Brinzolamide 1% plus Brimonidine 0.2% Fixed Combination (BBFC) therapy and separate concomitant Brinzolamide 1% and Brimonidine 0.2% therapy in patients of POAG and OHT.…”
Section: Discussionsupporting
confidence: 70%